IEEE INFOCOM 2014 - IEEE Conference on Computer Communications 2014
DOI: 10.1109/infocom.2014.6848181
|View full text |Cite
|
Sign up to set email alerts
|

Is it worth to be patient? Analysis and optimization of delayed mobile data offloading

Abstract: Operators have recently resorted to WiFi offloading to deal with increasing data demand and induced congestion. Researchers have further suggested the use of "delayed offloading": if no WiFi connection is available, (some) traffic can be delayed up to a given deadline, or until WiFi becomes available. Nevertheless, there is no clear consensus as to the benefits of delayed offloading, with a couple of recent experimental studies largely diverging in their conclusions. Nor is it clear how these benefits depend o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…This is known as mobile data and computation offloading. Several works have identified the benefits of WiFi data offloading [13][14][15]. The work in [13] showed that deferring the uploading tasks until WiFi access points are available can save the energy of smartphones.…”
Section: Abundance Of Spare Resources In D2d Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…This is known as mobile data and computation offloading. Several works have identified the benefits of WiFi data offloading [13][14][15]. The work in [13] showed that deferring the uploading tasks until WiFi access points are available can save the energy of smartphones.…”
Section: Abundance Of Spare Resources In D2d Networkmentioning
confidence: 99%
“…• Connectivity-aware task scheduling without our credit system: At the start of each task period, the supernode at BS will perform task scheduling calculation according to Algorithm 1 without our blockchain-based credit system. • Connectivity-aware task scheduling with our credit system: This is very similar to the above case, except that our blockchain-based credit system is added in to enforce fairness, as illustrated in (15).…”
mentioning
confidence: 99%
“…is can be seen as an enforced delay until a WiFi access point is encountered to o oad the cellular connection to a less loaded radio access technology [4,19], or until to reach peer nodes in a P2P infrastructure [6]. For example, Balasubramanian et al [4] develop a system to augment mobile 3G capacity with WiFi, using two key ideas: delay tolerance and fast switching.…”
Section: Related Workmentioning
confidence: 99%
“…Most of related works [4,6,19] require the user to move to encounter new base stations and see new caches. is is problematic as most users exhibit a nomadic behavior, staying in the same location for long periods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation